(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Rational numbers play a fundamental role in mathematics as they form the bridge between whole numbers and real numbers. They are defined as numbers that can be expressed as the quotient of two integers, where the denominator is not zero. This article explores the definition, history, properties, classification, and applications of rational numbers, while also examining their role in everyday life and mathematical problem-solving. The importance of rational numbers lies not only in theoretical mathematics but also in their practical applications, ranging from financial calculations to scientific measurements. This paper also provides an overview of the relationship between rational and irrational numbers, emphasizing their collective role in forming the set of real numbers.